PERISTIWA EKTREM DARI PROFITABILITAS, LEVERAGE, DAN IMPLIKASINYA TERHADAP RETURN SAHAM - Rio Nardo; Laynita Sari (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2021)
The economic crisis caused by the COVID-19 pandemic is more severe than the 1998 crisis. A very serious threat is the decline in the value of the investment in Indonesia. This decrease will have a direct impact on the company's financial performance and indirectly also result in the distribution of financial levels (returns) to shareholders. This research aims to test the effect of profitability and leverage on stock returns. The estimation method used in this study is the regression of panel data. The results showed that profitability has a positive and significant effect on the return of shares in companies listed on the Indonesia Stock Exchange. However, empirically there was no leverage influence on the return stock